Development of a Group Counseling Model Using the CBT-AD Approach to Improve Coping Compliance with Taking Antiretriviral Drugs (ARV) in HIV/AIDS Patients - Alfitri, Alfitri; Neviyarni, Neviyarni; Firman, Firman; Rihaliza, Rihaliza (Frontiers on Healthcare Research, 2026)
Background: Coping adherence to taking ARV medication is defined asstrategies and mechanisms that individuals use to deal with challenges associated with ARV treatment. This study aims to develop a group counseling model using the CBT-AD approach that is valid, practical, and effective in improving coping with ARV medication adherence. Methods: This study is a developmental research employing a modified version of the ADDIE model (analyze, design, development, implementation, and evaluation). The product's validity is assessed by five experts, while its practicality is evaluated by five counselors. Additionally, the effectiveness of the product is measured through data gathered from eight test subjects. In this study, the data analysis for the needs analysis stage involved employing descriptive statistical analysis. Results: Based on the research results, the CBT-AD group counseling model that was developed met the valid, practical, and effective criteria for improving coping with adherence to taking ARV medication in HIV/AIDS patients. The implementation of the CBT-AD group counseling model that was developed, there was a tendency for positive changes after being given CBT-AD group counseling. Statistical analysis and tracking of the end conditions of coping with ARV medication adherence proved that the application of the CBT-AD group counseling model was effective for increasing coping with ARV medication adherence in HIV/AIDS patients. Conclusion: This finding is an alternative solution in order to improve coping with adherence to taking ARV drugs and be able to live a life in the future.